Document details - A numerical model for the analysis of the bearings of a diesel engine subjected to conditions of wear and misalignment (2021)
In the present work, a numerical model is developed to investigate the influence of wear and misalignment on the bearings of a stationary diesel engine. The model implemented considers the effects of surface wear on the bearing, cavitation effects, and surface roughness. For the numerical analysis, changes in the surface roughness of σ = 0.75 µm, σ = 1 µm, and σ = 1.25 µm are defined, and changes in the bearing load of 50%, 75%, and 100%. The results demonstrated that increasing the surface roughness intensifies the bearing wear, which represents 18% and 140% of the bearing clearance for the roughness of σ = 1 µm and σ = 1.25 µm, respectively. Additionally, the surface roughness causes a considerable increase in the bearing wear rate. The results described a maximum wear rate of 20 µm/s. In general, increasing the bearing load by 25% doubles the hydrodynamic pressure conditions increases friction force by 33%, and reduces lubrication film thickness by 12%. The analysis of the angle of deflection, φx and φy, shows that the moment and the degree of misalignment tend to increase significantly with the increase in the magnitude of the angle φy. Negative angles of deflection, φx, produce a greater increase in the degree of misalignment and the moment. This implies a greater chance of contact with the bearing surface. In conclusion, the proposed methodology serves as a reliable tool to simultaneously evaluate key parameters on the tribological behavior of bearings that further extend their endurance and minimize wear damage.